2010
DOI: 10.1124/mol.110.066506
|View full text |Cite
|
Sign up to set email alerts
|

ATP Induces Synaptic Gene Expressions in Cortical Neurons: Transduction and Transcription Control via P2Y1 Receptors

Abstract: Studies in vertebrate neuromuscular synapses have revealed previously that ATP, via P2Y receptors, plays a critical role in regulating postsynaptic gene expressions. An equivalent regulatory role of ATP and its P2Y receptors would not necessarily be expected for the very different situation of the brain synapses, but we provide evidence here for a brain version of that role. In cultured cortical neurons, the expression of P2Y 1 receptors increased sharply during neuronal differentiation. Those receptors were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 54 publications
(109 reference statements)
7
16
0
Order By: Relevance
“…1A). P2Y 1 R, P2Y 2 R, P2Y 4 R, and P2Y 6 R were detected in both E18 and adult cortex, consistent with previous reports (Webb et al, 1998;Moore et al, 2001;Siow et al, 2010). Quantitative realtime PCR further revealed that the relative levels of these different P2YR mRNAs increased from embryonic to adult stages (Fig.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…1A). P2Y 1 R, P2Y 2 R, P2Y 4 R, and P2Y 6 R were detected in both E18 and adult cortex, consistent with previous reports (Webb et al, 1998;Moore et al, 2001;Siow et al, 2010). Quantitative realtime PCR further revealed that the relative levels of these different P2YR mRNAs increased from embryonic to adult stages (Fig.…”
Section: Resultssupporting
confidence: 91%
“…To specifically examine neuronal P2Y 2 R, primary cortical neurons were used as a model (Brewer, 1995;Siow et al, 2010). In preparations of neuron cultures, glial cells can often be found, and astrocytes are known to express P2YR subtypes such as P2Y 2 R and P2Y 4 R (Abbracchio and Ceruti, 2006;Fischer and Krügel, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations